Implementasi Metode Tanya Jawab Dalam Meningkatkan Kemahiran Berbicara Siswa Kelas XII Di Madrasah Aliyah Hasyim Asy’ari, Jogoroto, Jombang - Umdatun Najahah; Lailatul Qomariyah (Menara Tebuireng, 2023)
Abstrak—the primary motivation behind this research stems from the deficiency observed in students' speaking skills. There exists a subset of students who experience fear and embarrassment during the learning process due to their perceived inadequacy in speaking skills. This lack of communication proficiency results in diminished student engagement within the learning journey. Consequently, the researcher intends to address the following inquiries 1. Strategies for enhancing the proficiency of class XII students' "maharah kalam" (speaking skills) at MA Hasyim Asy'ari (MAHASY) , Jogoroto, Jombang.2. Implementing the question and answer technique in the context of twelfth-grade students at MA Hasyim Asy'ari, Jogoroto, Jombang..3. Evaluation of the advantages and drawbacks associated with employing the question and answer method for class XII students at MA Hasyim Asy'ari, Jogoroto, Jombang.The research adopts a qualitative approach, involving participation from students at MA Hasyim Asy'ari, located in Jogoroto, Jombang, along with Arabic teachers and school principals. Data collection methods encompass interviews, observations, and documentation. Data credibility is reinforced through triangulation, while the data analysis process encompasses data collection, reduction, presentation, and conclusion drawingThe findings of this study underscore endeavors aimed at enriching Arabic language speaking skills through techniques such as the question and answer method and public speaking exercises. Barriers to improving Maharah Kalam include the absence of LCD screens for enriching Arabic vocabulary through multimedia, as well as a lack of student self-assurance. Solutions involve implementing the question and answer method and organizing extracurricular activities to enhance Arabic language lessons. The outcomes of employing the question and answer method indicate progress in developing and amplifying language skills, expanding vocabulary, and fostering a greater affinity for the Arabic language. Keyword: : answer and question metode¸ speaking skills